The Problematics of Qur'an Teaching in Singapore's Half-Time Madrasah - Tokyan, Muhaimin Bin; Zamsiswaya (Program Studi Magister Pendidikan Agama Islam, 2024)
The half-time madrasah is an outgrowth of the earliest institutions of Islamic learning in Singapore. Half-term madrasah offers religious education for students attending mainstream schools. The half-term madrasa curriculum uses an Islamic religious education model called